Class Struggle In Bong Joon-Ho’s Film Parasite: An Analysis by Using Marxist Theory - Natasha Fabrianne; Didik Sucahyo; Ida Wardani (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2022)
Class Struggle in Bong Joon-ho’s Film Parasite: An Analysis by Using Marxist Theory. Class struggle is the continual conflict between the capitalist and working classes for economic and political power. In this study, the researcher will analyze the class struggle in Bong Joon-ho’s film Parasite by using Marxist theory. This study will be using descriptive qualitative research as its design. The purposes of this study are: 1) to find out the portrayal of social condition of the lower class in Bong Joon-ho’s film Parasite; 2) to find out the classification of social class in Bong Joonho’s film Parasite; 3) to find out the impacts of the class struggle toward the upper class and lower class in Bong Joon-ho’s film Parasite; 4) to find out if there is any specific behavior that the upper class frequently do to the lower class in the Bong Joon-ho’s film Parasite. The data in this study will be analyzed by using Miles and Huberman’s theory, which consists of three flows of activity: data reduction, data display, and conclusion drawing/verification. The result of this study shows that Bong Joon-ho’s film Parasite portrays the social condition of the lower class as the working class for the proletariat. In this film, the classification of social class is divided into two classes: the lower class, which is the Kim family and the upper class, which is the Park family. The impacts of class struggle that happened in this film are the Kim family’s jealousy and desire to infiltrate and creep into the Park family’s house, which resulted greed and violence. There is also a specific behaviorthat the upper class frequently do to the lower class in this film, which is the upper class’ act of being annoyed by the lower class’ smell.